2015
DOI: 10.1111/are.12746
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion ofVibriospp. by an antagonistic marine actinomyceteStreptomyces rubrolavendulaeM56

Abstract: A marine actinomycete Streptomyces rubrolavendulae M56 isolated from the sediments of Bay of Bengal and displaying biogranulation property was used for the study. The strain showed antagonistic property against vibrios, the opportunistic pathogens in aquaculture. The efficacy of the biogranules of actinomycete M56 in competitive exclusion of Vibrio spp. was tested both in vitro and in vivo. Streptomyces rubrolavendulae M56 biogranules could significantly exclude the pathogenic Vibrio spp. in co-culture experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…It is also worth noting that Vibrio strains were only detected in the initial control and the final depurated control but not in the Streptomyces-treated groups, suggesting a role of these probiotics on the elimination of this micro-organism. This exclusion of Vibrio by Streptomyces strains has already been shown in vitro and in vivo by other authors in Penaeus monodon (Das et al 2010;Augustine et al 2015). A recent study, which supports the probiotic effect of Streptomyces RL8 and N7 in C. sikamea, revealed that these strains were able to significantly decrease Vibrio count in Litopenaeus vannamei hepatopancreas, modulate host microbiota and improve its growth parameters and immune response.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is also worth noting that Vibrio strains were only detected in the initial control and the final depurated control but not in the Streptomyces-treated groups, suggesting a role of these probiotics on the elimination of this micro-organism. This exclusion of Vibrio by Streptomyces strains has already been shown in vitro and in vivo by other authors in Penaeus monodon (Das et al 2010;Augustine et al 2015). A recent study, which supports the probiotic effect of Streptomyces RL8 and N7 in C. sikamea, revealed that these strains were able to significantly decrease Vibrio count in Litopenaeus vannamei hepatopancreas, modulate host microbiota and improve its growth parameters and immune response.…”
Section: Discussionsupporting
confidence: 78%
“…; Augustine et al . ). A recent study, which supports the probiotic effect of Streptomyces RL8 and N7 in C. sikamea , revealed that these strains were able to significantly decrease Vibrio count in Litopenaeus vannamei hepatopancreas, modulate host microbiota and improve its growth parameters and immune response.…”
Section: Discussionmentioning
confidence: 97%
“…However, less attention has been put on the use of Actinobacteria as probiotics in aquaculture despite being widely known as prolific producer for secondary metabolites, particularly the genus ( Butler, 2008 ). The genus Streptomyces demonstrated promising results as probiotics ( Das et al, 2010 ; Augustine et al, 2015 ). This review aim to discuss the prospects of using Streptomyces as a probiotic candidate in aquaculture.…”
Section: Probioticsmentioning
confidence: 99%
“…Marine actinomycetes are among those promising candidates by virtue of their ability to produce a wide variety of antibiotics and extracellular enzymes (Barka et al, ; Prakash et al, ). In fact, some studies have shown that marine strains of the genus Streptomyces increased growth, survival and resistance to disease in the shrimp Penaeus monodon (Augustine, Jacob, & Philip, ; Das, Lyla, & Ajmal Khan, ; Das, Ward, & Burke, ).…”
Section: Introductionmentioning
confidence: 99%